Space counts! Brain correlates of spatial and numerical representations in synaesthesia. (January 2020) - Arend, Isabel; Yuen, Kenneth; Ashkenazi, Sarit; Henik, Avishai
Abstract: Over-learned semantic representations, such as numbers, are strongly associated with space in normal cognition, and in the phenomenon called number–space synaesthesia. In number–space synaesthesia, numbers are linked to spatial locations in an idiosyncratic way. Synaesthetes report numbers as belonging to a specific location, or feelings that a specific location is the right location for that number . What does really differentiate synaesthetes from non-synaesthetes with respect to their number–space representation? Here we present a number–space synaesthete, MkM, whose number–space representation dramatically differs from that of controls. We examined the impact of spatial distance with respect to MkM's mental number line (MNL), and numerical distance with respect to the conceptualized horizontal representation of numbers. In a behavioural experiment, MkM and controls performed number comparison tasks in which they reported either the larger numerical value (number task) or the larger stimulus (physical task) (Experiment 1). A spatial distance effect was found only for MkM. In a brain imaging experiment, MkM and controls compared a single presented digit with an internal reference (Experiment 2). Consistent with the behavioural results, spatial distance elicited significant brain activations only for MkM in different cortical sites including the left supramarginal gyrus. Numerical distance elicited significant brain activations only for controls in the left somatosensory cortex and in the right operculum. We propose that two types of representation are accessed in synaesthesia: one derived by the semantic coding of numbers across space (described by the MNL), and an explicit spatial representation derived from the position of number within the synaesthetic association. The level of overlap between these two forms of representation depends on the shape of the synaesthetic number–space association.